Kompetensi Pegawai: Pengaruh Pelatihan Terhadap Peningkatan Sikap Penyelenggara Pelatihan dalam Menjalankan Tugas - Sasono, Anton (Inovasi: Jurnal Diklat Keagamaan, 2024)
The purpose of this research is to determine the effect of training on improving the attitude of training organizers in carrying out training tasks at the Surabaya Religious Education and Training Center. This research uses a quantitative approach with a survey method. Data collection in this study used Saturated Sampling technique on a population of employees who had attended training. To analyze the data, path analysis techniques were used. The instrument used was a questionnaire on the variables of attitude towards tasks and training. This research proves that improving attitudes towards tasks is directly positively influenced by training, meaning that the implementation of training influences improving attitudes towards tasks